Numerical simulation of pollutant dispersion near obstacle based on k - ɛ turbulence closure scheme - Hai, Duong Ngoc; Duc, Nguyen The (Vietnam Journal of Mechanics, 2002)
To simulate the wind field, pollutant transport and dispersion near an obstacle a numerical code based on the k - Ɛ turbulence model has been built. Beside the standerd k - Ɛ, two other modifications proposed by Detering & Etling and Duynkerke are also considered. The calculation results are verified based on the measurement data of von Karman Institute for Fluid Dynamics (Belgium). Modifications of the turbulent Schmidt number were carried out in order to match the measured results. The code was used to investigate the influence of the recirculation zone behind a building of cubical shape on the transport and disersion of pollutant. For a stack behind and near the obstacle, some conclusions about the effect of the stack height and stack location were derived